Relationship between non-suicidal self-injury behavior, emotional dysregulation, and depressive symptoms among adolescents with childhood trauma experiences - FENG Jing; HAI Fan; QIAO Jing; LI Ximiao; KOU Xuefang; YANG Shichang (Guangxi Yike Daxue xuebao)
Objective To explore the relationship and underlying mechanisms between childhood trauma and non-suicidal self-injury (NSSI) behavior among adolescents. Methods A cross-sectional survey was conducted among 1, 188 junior high school students from Zhumadian and Xinxiang in Henan Province using a General Information Questionnaire, the Childhood Trauma Questionnaire-Short Form (CTQ-SF), the Patient Health Questionnaire-9 (PHQ-9), Brief Vession of the Difficulties in Emotion Regulation Scale-16 (DERS-16), and the Adolescent Non-Suicidal Self-Injury Assessment Questionnaire (ANSAQ). Descriptive statistics and Pearson correlation analysis were conducted using SPSS 27.0, while structural equation modeling was employed using AMOS 24.0 to analyze mediation effects. Results Among 1, 094 junior high school students, the detection rate of childhood trauma was 31.08%, the detection rate of moderate depression and above was 18.01%, and the detection rate of NSSI was 21.94%. ANSAQ scores were significantly positively correlated with PHQ-9 scores, CTQ-SF scores and DERS-16 scores, PHQ-9 scores were significantly positively correlated with CTQ-SF scores and DERS-16 scores, and CTQ-SF scores were significantly positively correlated with DERS-16 scores. Emotional dysregulation and depressive symptoms served as both separate and chained mediators between childhood trauma and adolescent NSSI behavior. Conclusion Childhood trauma can predict adolescent NSSI behavior through the mediating roles of emotional dysregulation and depressive symptoms, as well as through a chained mediation effect involving both emotional dysregulation and depressive symptoms.